Greenhouse evaluation of sagassum seaweed as a potting medium for vegetablesTT - Évaluation à effet de serre des algues sargasses comme milieu de mise en pot pour les légumes - Bridgemohan, Puran (Université des Antilles. Service commun de la documentation (2015-....), 2016)
Sargassum [Sargassum natans and S. fluitans] algae can be classified as a perennial invasive weed problem in all Caribbean islands. It has been shown to affect fishermen, bathers and tourists. It is expensive to remove, in addition to its unpleasant smell that hinders cleaning operations. The University of Trinidad and Tobago, on the BAFT campus, is conducting a series of activities to find appropriate uses of algae as feed, substrate and enhancement. This study aimed to assess the relevance of algae as a growing medium for sweet pepper production [Capsicum annuum var. annuum] using different percentages of weeds (0, 25, 50 and 100%) with greenhouse soil. Crop growth, development and yield were monitored.